Validity of short form 36 (SF-36) Indonesian version on rheumatoid arthritis patients - Laras Novitasari; Dyah Ariyani Perwitasari; Sudewi Khoirunisa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background: Rheumatoid arthritis is a chronic disease that decrease the function of the joint. It usually occurs on the feet and hands which may decrease the quality of one’s life. A valid and reliable instrument is needed to measure patients’ quality of life. SF-36 is a generic instrument to measure patients quality of life which is widely used in many diseases. Objective: This study is aimed to get valid and reliable Indonesian version of SF-36 questionnaire. Methods: We conducted this study in an observational cross-sectional design. Reliability was measured by Cronbach alpha parameter (>0.7). The validation processes included known group validity, convergent validity, and discriminant validity which are part of construct validity. Results: We recruited 24 RA patients in this study. All the domains met the reliability parameter, except for vitality function (Cronbach alpha : 0.52). The result of convergent and discriminant validities are good in almost all domains, except for questions number 16, 27, and 35 which did not meet discriminant validity and the number 9 which did not meet convergent and discriminant validity. The Known Group Validity test on gender showed that there was no statistically significant difference (ρ >0.05). However, there are significant differences based on general health between age groups, and based on pain and role limitation due to emotional function between educational status. Conclusion: The Indonesian version of SF-36 in general can be used for measuring rheumatoid arthritis patients’ quality of life.